(untitled) (CIPEEX, 2025)
Introduction: Acute abdomen during pregnancy is a challenging emergency with potential maternal and fetal risks. The main surgical causes are appendicitis, biliary disease, and adnexal torsion, with laparoscopy increasingly considered safe across all trimesters when proper technical adjustments are applied. Objective: To systematically review the evidence on surgical approaches for acute abdomen in pregnant women, focusing on maternal and fetal outcomes. Methodology: A systematic review was conducted in PubMed, SciELO, and BVS databases (2000–2025). Search terms included “pregnancy,” “acute abdomen,” “laparoscopy,” “appendicitis,” “cholecystitis,” and “adnexal torsion.” We included guidelines, systematic reviews, cohorts, and relevant series. Outcomes analyzed were maternal complications, fetal loss, preterm delivery, and length of stay. Results: Evidence shows that appendectomy should not be delayed, with laparoscopy presenting outcomes comparable or superior to laparotomy. In biliary disease, laparoscopic cholecystectomy during pregnancy reduces adverse outcomes and readmissions compared to conservative management, regardless of trimester. Adnexal torsion is best treated with laparoscopic detorsion and ovarian preservation. Imaging should prioritize ultrasound and Magnetic Resonance Imaging with Computed Tomography reserved for critical cases. Guidelines (Society of American Gastrointestinal and Endoscopic Surgeons, American College of Obstetricians and Gynecologists, National Institute for Health and Care Excellence, Royal College of Obstetricians and Gynaecologists) converge in recommending laparoscopy as safe in all trimesters, using 10–15 mmHg pneumoperitoneum, left lateral tilt after the first trimester, and fetal monitoring when viable. Conclusion: Surgical treatment of acute abdomen in pregnancy should not be postponed. Laparoscopy, when available and performed by experienced teams, is safe and often superior regarding recovery and recurrence prevention. Early diagnosis and appropriate imaging are essential to optimize maternal and fetal outcomes.